Gastric Lymphoma : A Literatur Review - Pramudya, Rian; Alami, Fathimah Nur; Sesariana, Mayumi Agestia; Balqis, Ananda Amirah; Fidelia, Puspa Zalika; Yulianti, Nur Afni; Bahraen, Raehanul (Jurnal Biologi Tropis, 2024)
Gastric lymphoma is the second most common finding in gastric malignancies worldwide. Gastric lymphoma is a lymphoproliferative disorder that originates in the stomach and encompasses various histological findings. In cases of gastric lymphoma, the most frequently diagnosed types are diffuse large B-cell lymphoma (DLBCL) and mucosa-associated lymphoid tissue (MALT) lymphoma. There is a known association between Helicobacter pylori infection and genetic mutations with the occurrence of gastrointestinal lymphoma. Treatment options for gastric lymphoma include observation, antibiotic therapy, radiation therapy, surgery, and chemotherapy. The therapy provided can be either monotherapy or a combination of treatments.